Sistema de auxílio à navegação para portadores de deficiência visual - Sato, Fernando Cirino (2014)
Aid to navigation systems can be used to help the visually impaired to perform daily tasks, such as their mobility and orientation. The objective of this project is to develop a prototype of an aid to navigation system for visually impaired people in indoors environments. The system has video sensors that detect obstacles ahead and markers containing points of interest that may be useful to the user, as doors and stairs. The methodology of this work involves selecting tools, computer vision techniques and digital image processing that may be useful to implement a prototype to validate the proposed work. As a result, a prototype was created that detects obstacles in real-time as well as points of interest.